A gestão escolar e a ética: um estudo de caso no Centro de Educação Básica Coronel José Epifânio das Chagas (Morada Nova-CE) - Martins, Raimunda Maria (2015)
This thesis has as its focus of study the theme ethics in the context of democratic and participative management, where the proposal is made to deal with the effectuation or not of an ethical school management, using as a field for appreciation the reality of the Cel. José Epifânio das Chagas Basic Education Center CEB, which is a unit of the municipal public education functioning in the educational system of Morada Nova, in the state of Ceará. The radius of investigation proposed is constituted by finding out how the ethical principles of a school management are made effective or not. This school management arrived at this condition through a process of indication and not through the legal path of educational legislation. That is, by instruments which characterize the democratization and participation of the elements involved in this context. Beginning with the cited focus of investigation, a survey was carried out of conceptions and commentaries of authors among whom can be cited, among other names, Hora, Libâneo, Lück, Gadoti, Gandim. Thereupon began the construction of a theoretical base with regard to the theme in study, characterizing this first moment of research as bibliographic. In the second moment one goes to the structuring of a philosophical base for the study, verifying the conceptions of Aristotle, Saint Augustine, and Immanuel Kant with regard to the concept of ethics and its application in the realm of formal basic education. Having in hand theoretical elements about democratic and participative management and a theoretical foundation, the investigation comes to the practical field which takes place based on an analysis of the reality of the above cited educational unit. The reading of documents such as the Brazilian National Education Legislation (Federal Constitution of 1988 and the National Education Bases and Guidelines Law LDB nº 9394/96) and of the school documents such as the Pedagogical Political Project and the Planning Report elaborated based on simple direct non structured observations made it possible to have a general view of the applicability of ethical principles in this educational institution. In this aspect it is pertinent to highlight that the research is of a documental character since the analysis proposed uses as the reference for appreciation the reading of the referred documents, which led to the final considerations and pointed to the need of continuing the studies in future projects of a doctoral program where one can broaden the scope of the radius of investigation and certainly the instruments of analysis.